(untitled) (Fiep Bulletin - online, 2012)
Aging, despite being a natural process the body undergoes several anatomical and physiological. The changes inherent in the process of aging does not mean illness, but the probability of the appearance of pathological processes increases with age. The objective of this study was to evaluate the relationship of hypertension and diabetes with the taste sensitivity in older adults who attend the best age groups. 50 volunteers were selected for study. He used solutions of sodium chloride (NaCl) and sucrose in increasing concentrations. It was concluded that the population is significant in elderly hypertensive patients (70%) in groups with greater age of Blumenau and Indaial, and that this prevalence is similar to that found in the rest of the country. It was also observed that the number of diabetics in the best age groups of Blumenau and Indaial, is high compared with the country, but is similar to that found for the southern region. However, it is difficult to find elderly diabetic patients without other associated diseases. In sensitivity to sweet and salty tastes in elderly normal, hypertensive and diabetic hypertensive and only, there was little difference in detection threshold for sucrose and NaCl solutions. With the exception of the detection threshold of the NaCl solution between normal and hypertensive elderly, which shows that elderly hypertensive patients have changes in taste sensitivity and that it could contribute to a high salt intake to high blood pressure.